In vitro and in vivo Characterization of Host–Pathogen Interactions of the L3881 Candida albicans Clinical Isolate - Sucupira, Pedro H. F.; Moura, Tauany R.; Gurgel, Isabella L. S.; Pereira, Tassia T. P.; Padovan, Ana C. B.; Teixeira, Mauro M.; Bahia, Diana; Soriani, Frederico M. (Frontiers in Microbiology, 2022)
Candida albicans is a human commensal fungus and the etiologic agent of nosocomial infections in immunocompromised individuals. Candida spp. is the most studied human fungal pathogen, and the mechanisms by which this fungus can evade the immune system affecting immunosuppressed individuals have been extensively studied. Most of these studies focus on different species of Candida, and there is much to be understood in virulence variability among lineages, specifically different C. albicans clinical isolates. To better understand the main mechanisms of its virulence variability modulated in C. albicans clinical isolates, we characterized L3881 lineage, which has been previously classified as hypovirulent, and SC5314 lineage, a virulent wild-type control, by using both in vitro and in vivo assays. Our findings demonstrated that L3881 presented higher capacity to avoid macrophage phagocytosis and higher resistance to oxidative stress than the wild type. These characteristics prevented higher mortality rates for L3881 in the animal model of candidiasis. Conversely, L3881 has been able to induce an upregulation of pro-inflammatory mediators both in vitro and in vivo. These results indicated that in vitro and in vivo functional characterizations are necessary for determination of virulence in different clinical isolates due to its modulation in the host–pathogen interactions.